2012
DOI: 10.5402/2012/318194
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Based Response to Exercise in Type 1 Diabetes

Abstract: While significant research has clearly identified sedentary behavior as a risk factor for type 2 diabetes and its subsequent complications, the concept that inactivity could be linked to the complications associated with type 1 diabetes (T1D) remains underappreciated. This paper summarizes the known effects of exercise on T1D at the tissue level and focuses on the pancreas, bone, the cardiovascular system, the kidneys, skeletal muscle, and nerves. When possible, the molecular mechanisms underlying the benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 147 publications
(173 reference statements)
0
16
0
Order By: Relevance
“…T1D is also associated with an increase in mortality at every age; by some estimates, mortality rates are 5–10 times higher among those with the disease . The early nature of T1D onset, with average diagnosis age being 14 years, results in a lifetime exposure not only to erratic blood glucose levels but also to increased risk of complications . The list of diabetes‐related complications is extensive and involves nearly every organ system, including the skeleton …”
Section: Introductionmentioning
confidence: 99%
“…T1D is also associated with an increase in mortality at every age; by some estimates, mortality rates are 5–10 times higher among those with the disease . The early nature of T1D onset, with average diagnosis age being 14 years, results in a lifetime exposure not only to erratic blood glucose levels but also to increased risk of complications . The list of diabetes‐related complications is extensive and involves nearly every organ system, including the skeleton …”
Section: Introductionmentioning
confidence: 99%
“…Physical activity in children is related to several positive health outcomes, both psychological and somatic, such as reduced cardiovascular disease risk factors (e.g., blood pressure, blood lipids; Saakslahti et al., ), better motor skill development (Fisher et al., ), improved psychosocial characteristics (Timmons et al., ), and a healthier body composition (Moore et al., ). Thus, physical activity is often recommended to patients with chronic diseases such as asthma, obesity, type 2 diabetes (T2D) and also to type 1 diabetes (T1D) patients to improve overall fitness and quality of life (Eijkemans et al., ; Stehno‐Bittel, ; Plotnikoff et al., ). Anyhow, it has recently been observed that children younger than 7 years with T1D are less physically active than healthy controls (Sundberg et al., ).…”
mentioning
confidence: 99%
“…In an animal study, the IL-6 induced Glucogon like Peptide-1(GLP-1) release that occurred during exercise improved insulin secretion during subsequent meals. Unfortunately, there are no human clinical studies directly measuring the effect of exercise on the health and function of islets [36].…”
Section: Effect Of Aerobic Exercise In Type 2 Dmmentioning
confidence: 99%
“…In Type 1 DM, only fewer reports have focused on the role of exercise, but more recent studies suggest that exercise improves blood glucose regulation, reduces the daily insulin dosage and decreases the risk of diabetes-associated complications in people with type 1DM 36 . There is clear evidence that aerobic exercises decrease the amount of required insulin to maintain glycemic control in people with type 1DM.…”
Section: Effect Of Exercise In Type 1 Dmmentioning
confidence: 99%